Techno-economic and life cycle analysis of a nano-enhanced flat plate solar collector for improved thermal performance - Shek Rahman; Salah Issa; Zafar Said; Ahmed Amine Hachicha (Energy Nexus)
This study evaluates the performance of flat plate solar collectors (FPSCs) enhanced with water-based Si₃N₄ nanofluids, focusing on thermal efficiency, economic feasibility, and environmental impact. Unlike widely studied Al₂O₃ and TiO₂ nanofluids, Si₃N₄ offers superior thermal conductivity (10–20 W/m·K) and lower density (2.6–3.2 g/cm³), making it a novel, underexplored candidate for FPSCs. Experimental results demonstrate that Si₃N₄ nanofluids at 0.09 % volume fraction achieve a 33 % improvement in thermal conductivity and 8 % enhancement in thermal efficiency compared to conventional water-based systems. The integration of Si₃N₄ reduces the required collector area by 6.1 %, enabling cost savings and compact system designs. Life cycle analysis reveals a 12 % reduction in carbon emissions and a 15 % shorter payback period (5.5 years), underscoring the environmental and economic viability of Si₃N₄ nanofluids. These advancements align with global sustainability goals, particularly SDG 7 (affordable and clean energy) and SDG 13 (climate action), by improving renewable energy technologies and reducing fossil fuel reliance.